Cooperative Societies in the Development Discourse of Ibadan, South-western Nigeria (2014)
Development remains a fundamental challenge confronting Nigeria. Hence, governments at all levels and development partners continue to experiment with different innovative frameworks and approaches. Many of the experimented approaches are however poorly understood leading to ineffective programming .among the strategies for development are cooperative societies. However, more scholarly works are needed to actually understand the development potentialities of cooperatives, sustainability of cooperative societies as agents of development as well as threats to their existence and effectiveness. Against this backdrop, this article examined issues that may impact development capabilities of cooperative societies in Ibadan.